Optimization of Cassava Waste from Bioethanol Post-Production through Bioactivity Process Consortium of Saccharomyces cerevisiae, Trichoderma viride and Aspergillus niger - Suryani , Yani (Asian Journal of Agriculture and Rural Development, 2013)
The result of laboratory analysis on bioethanol waste shows nutritional and anti-nutritional content (HCN). Based on it, in order to prevent environment damage then performed a bioconversion of bioethanol waste for base material of sheep forage by fermented previously using consortium of Saccharomyces cerevisiae, Trichoderma viride, and Aspergillus niger to eliminate the waste anti-nutritional content and increase nutritional content. This research used Completely Randomized Design (CRD) factorial pattern with two factors and three replications. The first factor was inoculum dose (D) and the second factor was variation of tested microorganisms (M). The variables measured were HCN content and nutrient content of fermented products, that were water content, protein content and crude fiber content by proximate analysis. Furthermore, the data was statistically analyzed by analysis of variance (ANOVA), and was there significant difference analyzed further by Duncan’s multiple range test of 5% level. Nutritional compositions of bioethanol waste from cassava that had been fermented by consortium of Saccharomyces cerevisiae, Trichoderma viride, and Aspergillus niger experienced changes compared to before fermentation. The results showed an increase in protein level, while fiber content, water content, and HCN content were decrease. Bioethanol waste from cassava fermented by Aspergillus niger and Saccharomyces cerevisiae (k3) with 2% inoculum dose had the highest protein content increase from 11.79% to 25.41% and had the lowest crude fiber content decrease from 16.4% to 12.84 %. The highest HCN decrease obtained from the fermentation of consortium Aspergillus niger and Trichoderma viride.